2014
DOI: 10.1123/ijsnem.2013-0054
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Dietary Protein During Caloric Restriction in Resistance Trained Lean Athletes: A Case for Higher Intakes

Abstract: Protein needs for energy-restricted resistance-trained athletes are likely 2.3-3.1g/kg of FFM scaled upwards with severity of caloric restriction and leanness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 52 publications
1
96
0
4
Order By: Relevance
“…During the cutting phase, participants increased their protein intake, as previously reported 1,2 , 94 The benefits of high-protein diets on weight loss have been highlighted by Leidy et al 95 Phillips & Van Loon 71 recommended increasing protein intake to 1.8 to 2.7 g/kg in order to optimize the ratio of fat-to-lean tissue mass loss during hypoenergetic periods. Additionally, Helms et al 96 suggested that 2.3-3.1 g/kg FFM is appropriate for lean, resistance-trained athletes in hypoenergetic conditions. However, it is important to note that, among the studies used to support high-protein diets in the mentioned reviews, only two used protein intakes over 2 g/kg 97,98 and only one compared the effects of different protein intakes.…”
Section: Discussionmentioning
confidence: 99%
“…During the cutting phase, participants increased their protein intake, as previously reported 1,2 , 94 The benefits of high-protein diets on weight loss have been highlighted by Leidy et al 95 Phillips & Van Loon 71 recommended increasing protein intake to 1.8 to 2.7 g/kg in order to optimize the ratio of fat-to-lean tissue mass loss during hypoenergetic periods. Additionally, Helms et al 96 suggested that 2.3-3.1 g/kg FFM is appropriate for lean, resistance-trained athletes in hypoenergetic conditions. However, it is important to note that, among the studies used to support high-protein diets in the mentioned reviews, only two used protein intakes over 2 g/kg 97,98 and only one compared the effects of different protein intakes.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been recent trends for even higher protein recommendations to promote health [103], support weight loss strategies [104], to preserve lean body mass (LBM) under hypocaloric situations [105], in resistance-type sports such as bodybuilding [106], and corporate sports performance programs [107]. That athletes, especially in strength and power sports, accomplish higher protein intakes has also been shown [108], with recent reports also highlighting the issue of extremely high protein intakes in some athletes [96,109].…”
Section: Eat As If You Could Save the Planet And Win!mentioning
confidence: 99%
“…Table 3 shows hypothetical amounts of meat (in this case beef) in reference to the (1) non-athlete recommended daily allowance (RDA) for protein [113]; (2) current athlete protein recommendation (~1.5 g/kg BW/day [97]); and (3) recently suggested athlete protein recommendations under energy restriction for weight loss (~2.5 g/kg BW/day [104,105]). It is assumed under this example, that 50% of dietary protein is supplied by meat.…”
Section: Eat As If You Could Save the Planet And Win!mentioning
confidence: 99%
“…Additionally, fat-free mass and positive nitrogen balance were better maintained in soldiers during exercise-induced energy deficits when protein intake doubled from 0.9 to 1.8 g/kg [63]. A recent systematic review determined that the optimal protein intake to maintain muscle mass during caloric restriction was 2.3-3.1 g/kg, with the caveat that the athlete's body composition prior to the energy deficit be considered [64]. These data seem to support the conclusion that in the case of athletes or soldiers in a hypocaloric state, protein intake above the RDA and as high as 2.3-3.1 g/kg may prevent lean body mass loss.…”
Section: Recommended Dietary Allowancementioning
confidence: 99%